Contributions to the Lepidoptera fauna of the Madeiran Islands 1. Introduction. - Karsholt, Ole (Contributions to Entomology = Beiträge zur Entomologie, 2000)
The present paper deals with the Madeiran Islands from a lepidopterological point of view. Short chapters summarize information on geography, geology, climate, and vegetation. The history of lepidopterological research in Madeira is presented, with references to additional literature. The origin of the approximately 300 species of Lepidoptera known from Madeira is briefly discussed, as are the problems with mislabeled material.KeywordsMadeira, Lepidoptera, lepidopterists, laurisilva.